Gregory of Nyssa: Contra Eunomium I, An English Translation with Supporting Studies. - Miguel Brugarolas (Editor) (Vigiliae Christianae, Supplements, 2018)
The Contra Eunomium is probably Gregory of Nyssa's most challenging work with regards to his theological and philosophical thought, and one that continues to draw the deeper attention of contemporary scholars. This volume devoted to Contra Eunomium I constitutes, in a certain way, a new version of the Proceedings of the 6th International Colloquium on Gregory of Nyssa (1988). It offers a revised English translation of Contra Eunomium I by S. G. Hall, accompanied by twenty-two supporting studies from a broad range of philological, philosophical, and theological perspectives. These studies include a selection of the most relevant papers of the 1988 Proceedings, supplemented with new contributions that explore relevant issues developed by contemporary research.